A comparative cross-sectional study on comparison of hyperkalemia measurement between blood gas analyzer in Emergency Department and main laboratory biochemistry analyzer in Hospital Universiti Sains Malaysia - Ismail, Mohd Helmie (2020)
Background: Potassium level is measured for patient with high risk of hyperkalemia in an emergency department (ED) using both blood gas analyser (BGA) and biochemistry analyser (BCA). The purpose of study to evaluate the correlation and agreement of hyperkalemia measurement between these two analysers. Methods and Materials: This is a prospective cross-sectional study was conducted at Hospital Universiti Sains Malaysia (HUSM) from Jun 2018 until May 2019. The blood samples were taken by single pricked from venous blood and were sent separately using 1-ml heparinized syringe and analysed immediately in the emergency department (ED) using BGA (Radiometer, ABL800 FLEX, Denmark) and another sample was sent to the main laboratory of HUSM and analysed by BCA (Architect, C8000, USA). Only patients who had potassium level ³ 5.0 mmol/L on blood gas results were included. The correlation and agreement were evaluated using Passing and Bablok regression, Linear Regression and Bland-Altman test. Result: A total of 173 sample pairs were included. The mean of potassium level based on BGA and BCA were 5.77 mmol/L (SD±0.74) and 6.05 mmol/L (SD±0.91) respectively. There was moderate correlation between two measurements (P<0.001, r: 0.36). The agreement between two measurements showed within acceptable mean difference which was 0.27 mmol/L with 95% limit of agreement was –1.21 mmol/L to 1.73 mmol/L. Conclusion: There is moderate correlation and acceptable agreement in hyperkalemia measurement between BGA to BCA. However, the BGA results tend to be lowered compared to BCA results. Therefore, the clinicians should use the BGA result with caution in certain clinical situation where time-is-of-the-essence to initiate treatment for hyperkalemia.